Differences in MB-COMT DNA methylation in monozygotic twins on phenotypic indicators of impulsivity - Smederevac, Snežana; Delgado-Cruzata, Lissette; Mitrović, Dušanka; Dinić, Bojana M.; Bravo, Toni-Ann T.; Delgado, Maria; Bugarski Ignjatović, Vojislava; Sadiković, Selka; Milovanović, Ilija; Vučinić, Nataša; Branovački, Bojan; Prinz, Mechthild; et al. (Frontiers in Genetics, 2023)
Epigenetic modifications of the membrane-bound catechol-O-methyltransferase (MB-COMT) gene may affect the enzymatic degradation of dopamine, and consequently, human behavior. This study investigated the association between MB-COMT DNA methylation (DNAm) differences in 92 monozygotic (MZ) twins with phenotypic manifestations of cognitive, behavioral, and personality indicators associated with reward-related behaviors and lack of control. We used pyrosequencing to determine the DNAm of the regulatory region of MB-COMT in saliva DNA. Results of intrapair differences in the percentage of MB-COMT DNAm at each of the five CpG sites show that there are associations between phenotypic indicators of lack of control and MB-COMT DNAm differences on CpG1, CpG2 and CpG4, suggesting the common epigenetic patterns for personality traits, cognitive functions, and risk behaviors.